Lignocellulose degradation in bacteria and fungi: cellulosomes and industrial relevance - Hsin, Kuan-Ting; Lee, HueyTyng; Huang, Yu-Chun; Lin, Guan-Jun; Lin, Pei-Yu; Lin, Ying-Chung Jimmy; Chen, Pao-Yang (Frontiers in Microbiology, 2025)
Lignocellulose biomass is one of the most abundant resources for sustainable biofuels. However, scaling up the biomass-to-biofuels conversion process for widespread usage is still pending. One of the main bottlenecks is the high cost of enzymes used in key process of biomass degradation. Current research efforts are therefore targeted at creative solutions to improve the feasibility of lignocellulosic-degrading enzymes. One way is to engineer multi-enzyme complexes that mimic the bacterial cellulosomal system, known to increase degradation efficiency up to 50-fold when compared to freely-secreted enzymes. However, these designer cellulosomes are instable and less efficient than wild type cellulosomes. In this review, we aim to extensively analyze the current knowledge on the lignocellulosic-degrading enzymes through three aspects. We start by reviewing and comparing sets of enzymes in bacterial and fungal lignocellulose degradation. Next, we focus on the characteristics of cellulosomes in both systems and their feasibility to be engineered. Finally, we highlight three key strategies to enhance enzymatic lignocellulose degradation efficiency: discovering novel lignocellulolytic species and enzymes, bioengineering enzymes for improved thermostability, and structurally optimizing designer cellulosomes. We anticipate these insights to act as resources for the biomass community looking to elevate the usage of lignocellulose as biofuel.